Prescription for the People : An Activist's Guide to Making Medicine Affordable for All - Quigley, Fran, 1962- (Book collections on Project MUSE., 2017)
"In Prescription for the People, Fran Quigley diagnoses our inability to get medicines to the people who need them and then prescribes the cure. He delivers a clear and convincing argument for a complete shift in the global and U.S. approach to developing and providing essential medicines -- and a primer on how to make that change happen."--